Kelebihan dan Kekurangan Model Pembelajaran Pondok Pesantren Modern di Masa Pandemi - Malik, Fatkhulloh Abdul; Muadhom, Mokhamad Choirul (JoEMS (Journal of Education and Management Studies), 2022)
Learning is essentially a learner's interaction with an educator. In the middle of the covid-19 pandemic,as well as with the world of education, teaching learning comes to a halt as the result of restrictions to break the chain of spreading the plague. In this case it is somewhat a problem for a number of boarding schools, which requires learning to be done online, but there are a number of boarding schools that continue to carry out their studies in person. Just like the one from Bahrul ‘Ulum Islamic Boarding School. The study employs a qualitative approach, where it tends to lead to a descriptive study method. A data process was conducted with interviews for some on the board, teachers, and santri as well as a questions of google forms sent via whatsapps to some santri guardians to see how the guardians responded to home-home-study sessions. Studies show that one problem is so brief on time that less effective study, and less effective on the study activities in the home that sometimes change the Settings,so on the part of the administration makes the activities loosening or flexible in execution, rule etc.